Stakeholder Engagement For Business Sustainability - Jamil Farhas, Rizqon; Rabialdyi, Fakhri; Laowe, Dhya Nadia (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2023)
Companies need to understand and manage relationships with stakeholders in achieving goals and prepare conflict reports that cover social, environmental and economic aspects in accordance with POJK No. 51/POJK.03/2017. The 3P (Profit, Planet, People) concept from Elkington (1997) emphasizes the balance between economic profit, environmental sustainability and social welfare. Binus Business School held a public lecture entitled